METHODOLOGY OF TEACHING HEDGING DEVICES IN ACADEMIC WRITING TO B2-LEVEL STUDENTS - G. R. Aminova (International Journal of Literature and Language Studies, 2026)
This article examines the methodology of teaching hedging devices in academic writing to B2-level students of English as a foreign language. Hedging is treated as a central feature of academic discourse because it helps writers make claims carefully, avoid overgeneralization, and present arguments in a balanced manner. Main forms of hedging are briefly discussed. It argues that B2-level learners often write overly direct statements because they have limited awareness of academic stance. A gradual teaching model is proposed, including awareness-raising, noticing, controlled practice, guided writing, peer feedback, and independent production.